Landslide detection system design internet of things based on 150 kv gianyar carrier - Pancane, IWayan Dikse; Fahreza, Risang Aji (Universitas Sarjanawiyata Tamansiswa, 2024)
Bali is one of the tourist destinations that is well known internationally, besides that Bali is also the door to the world to get to know Indonesia. To support the tourism industry on the island of the gods, PLN personnel are expected to be able to provide the best service for consumers. So the Bali transmission system is required to provide a reliable transmission system in order to provide World Class Service to electricity consumers in Bali. One way to support the continuity of distribution is by monitoring the condition of the transmission tower, especially on towers that are at a height and slope, for example on hills, mountains, on the edge of ravines, etc. which are prone to ground movement or landslides. The current monitoring method is less effective for monitoring critical tower conditions and prone to landslides that can occur at any time, especially in the rainy season and extreme weather. The demand for a reliable transmission system makes the authors think of having monitoring equipment that can work in real time so that the condition of the tower or ground movement around the tower can be detected as quickly as possible. The information transmission carried out by the tool utilizes the LoRa (Long Range) module which functions as a sensor data sender to overcome the unavailability of cellular networks because the tower area on the transmission network is mostly located in forest areas.